2007
DOI: 10.1021/ja0703527
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of Hydrogen Storage Characteristics of Covalent-Bonded Graphenes

Abstract: We performed first-principles calculations to investigate the hydrogen storage characteristics of carbon-based 3-D solid structures, called covalently bonded graphenes (CBGs). Using the density functional method and the Møller-Plesset perturbation method, we show that H2 molecular binding in the CBGs is stronger than that on an isolated graphene with an increase of 20 to approximately 150% in binding energy, which is very promising for storage at ambient conditions. We also suggest that the CBGs of appropriate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
140
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 163 publications
(145 citation statements)
references
References 31 publications
5
140
0
Order By: Relevance
“…Recently, several computational studies proposed that transition metal ͑TM͒ dispersed in nanomaterials or polymers can bind hydrogen molecules with appropriate strength so that the storage system filled with such TM complexes can operate at ambient conditions with enough storage capacities. [3][4][5][6][7][8] It was shown that the hydrogen binding energy ranges from 0.3 to 0.7 eV depending on the metal type, and that the effective storage capacity can reach as high as about 6 wt %. [3][4][5][6][7][8] The Kubas interaction between TM atoms and hydrogen molecules was shown to be responsible for enhanced hydrogen adsorption energy.…”
mentioning
confidence: 99%
“…Recently, several computational studies proposed that transition metal ͑TM͒ dispersed in nanomaterials or polymers can bind hydrogen molecules with appropriate strength so that the storage system filled with such TM complexes can operate at ambient conditions with enough storage capacities. [3][4][5][6][7][8] It was shown that the hydrogen binding energy ranges from 0.3 to 0.7 eV depending on the metal type, and that the effective storage capacity can reach as high as about 6 wt %. [3][4][5][6][7][8] The Kubas interaction between TM atoms and hydrogen molecules was shown to be responsible for enhanced hydrogen adsorption energy.…”
mentioning
confidence: 99%
“…The metal-hydrogen binding energy and ratio look very promising with respect to capacity and release temperature. [4][5][6][7][8][9][10][11] However, the issue of structural stability and poor reversibility in TM dispersion has been a major concern as TM atoms tend to easily aggregate instead of being atomistically dispersed. 12,13 Strong metal cohesion is believed to be responsible for the aggregation.…”
mentioning
confidence: 99%
“…As a way to overcome such clustering, it was suggested to increase the binding strength between metal and dispersant materials by introducing structural or chemical defects. 10,11 For example, boron doping in graphitic materials was shown to improve dramatically the metal dispersion and the hydrogen adsorption. 11 In this letter, we study pyridinelike nitrogen doped graphene ͑PNG͒ as an effective medium for TM ͑Sc, Ti, and V͒ atomic dispersion.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…157,158 By calculations of graphene buckling, convex regions in corrugated graphene are energetically favorable for hydrogen binding. 159 A corrugated graphene multilayer system can reversibly store hydrogen with a maximum capacity of 8 wt% under ambient conditions by controlling the local curvature.…”
Section: Gas Adsorptionmentioning
confidence: 99%